Rheology and crystallization behavior of polypropylene and high‐density polyethylene in the presence of a low molar mass polyethylene. Issue 4 (14th June 2019) - Robert, Michaël; Fulchiron, René; Cassagnau, Philippe
Abstract: The rheological behavior and crystallization behavior of high density polyethylene (HDPE) and polyethylene (PE) oligomer (HDPE/PE oligomer) and polypropylene (PP) and polyethylene oligomer (PP/PE oligomer) binary blends were investigated in this study. Batch processing along with rheological model experiments revealed that molecular diffusion is the dominating mechanism in the homogenization of such blends. Further rheological characterization and modeling (using the Carreau‐Yasuda equation) allowed to demonstrate that the PE oligomer is miscible in both polymers, but that saturation may occur at high concentrations. Thermal analysis as well as polarized light and electronic microscopy showed that both systems undergo solid‐liquid phase separation upon cooling, with direct consequences on the mechanical properties of the blends. The concentrations at which saturation (in the melt), phase separation (upon cooling), and degradation of the mechanical properties occur were found to be dependent on the nature of the polymer; around 20 to 30 wt% for HDPE and 5 to 10 wt% in the case of PP. Abstract : A large number of processing aids that are used in the formulation of polyolefins consist of hydrocarbon derivatives such as oils and waxes. The main difficulties associated with those blends are the low viscosity ratio between the additive and the polymer resin in the molten state as well as the potential phase separation in the solid state. The aim of this article is therefore to investigate the miscibility and morphology developments occurring during the processing and solidification of PP and HDPE in the presence of a low molar mass PE oligomer.